Amyotrophic lateral sclerosis mortality rates in Latin America and the Caribbean: a meta-analysis. Issue 7 (2nd October 2022) - Erazo, Daniells; Luna, Jaime; Preux, Pierre-Marie; Medina, Marco Tulio; Magne, Julien; Boumediene, Farid; Couratier, Philippe
Abstract: Background : Recent studies have described a low occurrence of Amyotrophic Lateral Sclerosis (ALS) in Latin America. Significant differences in ALS risk have been reported among ethnic populations in the region. We conducted a meta-analysis using population-based data to describe ALS mortality rates in Latin America. We explored sources of heterogeneity among key covariates. Methods : National mortality registries from Latin American countries were searched to identify ALS deaths according to the International Classification of Diseases (ICD-9: code 335.2 and ICD-10: code G12.2). Crude and standardized mortality rates were calculated. A random-effect meta-analysis was conducted to estimate pooled mortality rates. Subgroup analysis was performed as a means of investigating heterogeneity. Results : Overall, 28, 548 ALS deaths and 819 million person-years of follow-up (PYFU) from ten Latin American countries were considered. Standardized mortality varied among countries. The highest mortality rates were observed in Uruguay and Costa Rica at 1.3 and 1.2 per 100, 000 PYFU, respectively. The pooled crude mortality rate was 0.38 (95%CI: 0.28–0.53) and the pooled standardized mortality was 0.62 (95%CI: 0.49–0.77) per 100, 000 PYFU. Heterogeneity was high (I2: 99.9%, Cochran's Q p < 0.001). Subgroup analysis showed a higher mortality rate among countries with a higher proportion of Caucasian populations and higher income levels. Conclusion : There is a lower ALS occurrence in Latin America compared to Europe and North America. This meta-analysis supports the hypothesis of a higher ALS risk among the Caucasian population. Further studies are needed to investigate the role of ancestral origins in ALS, taking socioeconomic status into consideration.